Substitute
. By the chain rule,
![(dy)/(dx) = (dy)/(dt)\cdot(dt)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/high-school/mjicyfxa1qtj81tj2qil5p3rbfmoh24i6w.png)
Now
, so
![(dy)/(dx) = \frac1x (dy)/(dt) \\\\ ~~~~~~~~ \iff (dy)/(dt) = x(dy)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/high-school/goyv4u3s7f84n95eh1v7mkne7c4tbcpyqf.png)
Differentiate both sides again to recover the second and third derivatives.
![(d^2y)/(dx^2) = -\frac1{x^2}(dy)/(dt) + \frac1x (d(dy)/(dt))/(dx) \\\\ ~~~~~~~~ = -\frac1{x^2}(dy)/(dt) + \frac1x \left((d(dy)/(dt))/(dt)\cdot(dt)/(dx)\right) \\\\ ~~~~~~~~ = -\frac1{x^2} (dy)/(dt) + \frac1{x^2}(d^2y)/(dt^2) \\\\ ~~~~~~~~ \iff (d^2y)/(dt^2) - (dy)/(dt) = x^2 (d^2y)/(dx^2)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5e0neaj4nfe8tuju2xta8wo7qd7554hzov.png)
![(d^3y)/(dx^3) = \frac2{x^3}(dy)/(dt) - \frac1{x^2}(d(dy)/(dt))/(dx) - \frac2{x^3} (d^2y)/(dt^2) + \frac1{x^2}(d(d^2y)/(dt^2))/(dx) \\\\ ~~~~~~~~ = \frac2{x^3} (dy)/(dt) - \frac1{x^2}\left((d(dy)/(dt))/(dt)\cdot(dt)/(dx)\right) - \frac2{x^3} (d^2y)/(dt^2) + \frac1{x^2}\left((d(d^2y)/(dt^2))/(dt)\cdot(dt)/(dx)\right) \\\\ ~~~~~~~~ = \frac2{x^3} (dy)/(dt) - \frac1{x^3} (d^2y)/(dt^2) - \frac2{x^3} (d^2y)/(dt^2) + \frac1{x^3}(d^3y)/(dt^3) \\\\ ~~~~~~~~ \iff (d^3y)/(dt^2) - 3 (d^2y)/(dt^2) + 2 (dy)/(dt) = x^3 (d^3y)/(dx^3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/gmmqujvljeg1nito5xmwll99ehjy66rv4q.png)
The ODE then transforms to a linear one,
![3\left((d^3y)/(dt^2) - 3 (d^2y)/(dt^2) + 2 (dy)/(dt)\right) + 28\left((d^2y)/(dt^2) - (dy)/(dt)\right) + 55(dy)/(dt) + 9 y = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/pv0hmd8a4ylzgpa3t8b90k9aqfhl0vrl73.png)
or using Lagrange's prime notation,
![3(y''' - 3y'' + 2y') + 28(y'' - y') + 55y' + 9y = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/v1xs7otvm9156wc748quimihm1v34j29mq.png)
![3y''' + 19y'' + 33y' + 9y = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/40vgoza5btpc8s24twosq65z2myktuaork.png)
The characteristic equation is
![3r^3 + 19r^2 + 33r + 9r = (r + 3)^2 \left(r + \frac13\right) = 0](https://img.qammunity.org/2023/formulas/mathematics/high-school/csqlnhwl62wl7v1vwa8ix4xecfizncpqa1.png)
with roots at
and
, so the general solution is
![y(t) = C_1 e^(-1/3\,t) + C_2 e^(-3t) + C_3 t e^(-3t)](https://img.qammunity.org/2023/formulas/mathematics/high-school/s7bk9wgqmpln18f7tu9xdweel1ejll6wpa.png)
Back in terms of
, we get
![\boxed{y(x) = C_1 x^(-1/3) + C_2 x^(-3) + C_3 x^(-3)\ln(x)}](https://img.qammunity.org/2023/formulas/mathematics/high-school/z10wrqo2ihp7s6g7leagmt2vtdevpz9mvb.png)